Intraductal fibroadenoma under the nipple in an 11-year-old female - Hayano, Fumiko (BioMed Central, 2014)
Recently, Chung et al. have reported the detailed clinicopathological features of an extremely rare case sharing similar histopathological characteristics with fibroadenomas, phyllodes tumours, intraductal papillomas or ductal adenomas, given the name of intraductal fibroadenomatosis, as an unusual variant of intracanalicular fibroadenoma. Herein we demonstrated a very unusual case of intraductal fibroadenoma of the breast with admixture of components of intracanalicular type fibroadenoma or benign phyllodes tumour and a smaller amount of intraductal papilloma, occupying the one duct and some adjacent ductules, presenting as a well-demarcated nodule.